Sensing Cells-Peptide Hydrogel Interaction In Situ via Scanning Ion Conductance Microscopy - Tikhonova, Tatiana N.; Kolmogorov, Vasilii S.; Timoshenko, Roman V.; Vaneev, Alexander N.; Cohen-Gerassi, Dana; Osminkina, Liubov A.; Gorelkin, Petr V.; Erofeev, Alexander S.; Sysoev, Nikolay N.; Adler-Abramovich, Lihi; Shirshin, Evgeny A. (Cells (Basel, Switzerland), 2022)
Peptide-based hydrogels were shown to serve as good matrices for 3D cell culture and to be applied in the field of regenerative medicine. The study of the cell-matrix interaction is important for the understanding of cell attachment, proliferation, and migration, as well as for the improvement of the matrix. Here, we used scanning ion conductance microscopy (SICM) to study the growth of cells on self-assembled peptide-based hydrogels. The hydrogel surface topography, which changes during its formation in an aqueous solution, were studied at nanoscale resolution and compared with fluorescence lifetime imaging microscopy (FLIM). Moreover, SICM demonstrated the ability to map living cells inside the hydrogel. A zwitterionic label-free pH nanoprobe with a sensitivity > 0.01 units was applied for the investigation of pH mapping in the hydrogel to estimate the hydrogel applicability for cell growth. The SICM technique that was applied here to evaluate the cell growth on the peptide-based hydrogel can be used as a tool to study functional living cells.